Sistemas de produção e aprendizagem organizacional: um estudo de caso em uma empresa de medidores de energia - Coelho, João Batista Soares (Universidade do Vale do Rio do Sinos, 2007)
This study purposes to analyze the learning processes under the individual, group and organizational level in an industrial production system that presents characteristics of both the Toyota model and the Volvo model. It derives from the presupposition that the autonomy of the worker in production level is favorable to organizational learning.The research is developed through a case study in an industry of energy measuring devices. The collected data consist of the search for similarities and divergences between the two management systems, besides investigating which characteristics corroborate to the individual, group and organization learning process. Bearing the theoretical framework that compares the Social-Technical System to the Toyota Production System, the work is taken to the field seeking to map the work structure of an organization holding as base the theoretical referential in question. Finally, this work presents a Case Study accompanied of an exploratory research with qualitative and quantitativ
Keywords: aprendizagem organizacional; equipes auto gerenciáveis; sistema sócio-técnico; Sistema Toyota de Produção; organizational learning; self-management teams; social-technical system; Toyota Production System; Ciências Sociais Aplicadas